Amore del corpo e amore dell’anima in due testi platonici - Napolitano, Linda M. (Peitho. Examina Antiqua, 2025)
In the Platonic Symposium the rhetorician Pausanias celebrates celestial love, directed to a greater degree to the soul rather than the body and which involves the lover and the beloved in the practice of a common virtue. This passage has been put in parallel with Alcibiades I, where Socrates maintains that authentic love is directed not towards the body but the soul. He says he loves Alcibiades with such a love: therefore he urges the young man to correspond to him by seeking to be “as beautiful as possible”, with an inner beauty that, unlike that of the body, will not fade. Undoubted textual analogies allow us to link the two texts: nevertheless the meaning of Socrates’ argument in Alcibiades I seems much deeper than that of Pausanias. It is based on the demonstration that man’s true self is the soul, capable of love and lovable only if is the object of constant care (epimeleia heautou). If anything, it is this philosophical thesis – as also the Phaedrus demonstrates as Platonic – that can establish the authenticity of Alcibiades I.